First record of the leafhopper genus Scaphomonus Viraktamath from Korea, with description of one new species (Hemiptera: Cicadellidae: Deltocephalinae) - Dutta, Nirmal Kumar; Kwon, Jin Hyung; Suh, Sang Jae; Kwon, Yong Jung (Zootaxa, 2020)
The leafhopper genus Scaphomonus Viraktamath, 2009 is reported from the Korean peninsula for the first time, based on the discovery of a new species: Scaphomonus naejangsanus sp. nov. A checklist and keys to world Scaphomonus species are given.